Association of Sustained Blood Pressure Control with Multimorbidity Progression Among Older Adults. Issue 9 (5th June 2020) - Bowling, C. Barrett; Sloane, Richard; Pieper, Carl; Luciano, Alison; Davis, Barry R.; Simpson, Lara M.; Einhorn, Paula T.; Oparil, Suzanne; Muntner, Paul
Abstract : BACKGROUND/OBJECTIVES: Due to the high costs and excess mortality associated with multimorbidity, there is a need to develop approaches for delaying its progression. High blood pressure (BP) is a common chronic condition and a risk factor for many additional chronic conditions, making it an ideal target for intervention. The purpose of this analysis was to determine the association between the level of sustained BP control and the progression of multimorbidity. DESIGN: Retrospective cohort study. SETTING: Antihypertensive and Lipid‐Lowering Treatment to Prevent Heart Attack Trial (ALLHAT) linked to Medicare claims. PARTICIPANTS: A total of 6, 591 ALLHAT participants with Medicare who had systolic BP (SBP) measurements at eight or more study visits. MEASUREMENTS: SBP control was categorized as lower than 140 mm Hg at less than 50%, 50% to less than 75%, 75% to less than 100%, and 100% of visits. Multimorbidity progression was defined by the number of incident chronic conditions, including arthritis, asthma, atrial fibrillation, cancer, chronic kidney disease, chronic obstructive pulmonary disease, coronary heart disease, dementia, depression, diabetes mellitus, heart failure, hyperlipidemia, osteoporosis, and stroke. Recurrent event survival analysis was used to calculate rate ratios (RRs) for the association of sustained SBP control with progression of multimorbidity. RESULTS: Rates of incident conditions per 10 person‐years (95% CIs) were 5.2 (5.1–5.4), 4.7 (4.5–4.8), 4.4 (4.2–4.5), and 4.0 (3.8–4.2) for participants with SBP control at less than 50%, 50% to less than 75%, 75% to less than 100%, and 100% of visits, respectively, over a median follow‐up of 9.0 years. Compared with participants with SBP control at less than 50% of visits, adjusted RRs (95% CIs) for multimorbidity progression were 0.90 (0.86–0.95), 0.85 (0.81–0.89), and 0.77 (0.72–0.82) for those with SBP control at 50% to less than 75%, 75% to less than 100%, and 100% of visits, respectively. CONCLUSIONS: Sustaining BP control may be an effective approach to slow multimorbidity progression and may reduce the population burden of multimorbidity.